The Role of Nasr’s Philosophy of Education in Addressing the Moral Crisis - Elok Nadiatun Naimah; Dyah Lutfiahsari Afifah; Muhammad Asrori (Majalah Ilmu Pengetahuan dan Pemikiran Keagamaan Tajdid, 2025)
The persistent moral decline in contemporary education underscores the inadequacy of existing pedagogical frameworks and the need for innovative alternatives. This study explores Seyyed Hossein Nasr’s philosophy of education as a novel paradigm for moral renewal, focusing on integrating ethical and spiritual values as the foundation of character formation. Using a qualitative conceptual design through a systematic literature review of Nasr’s seminal works and relevant educational theories, the study identifies his holistic framework which harmonizes intellectual, emotional, and spiritual dimensions as a robust basis for moral education. The findings demonstrate that Nasr’s philosophy advances both theoretical discourse and provides practical insights for curriculum development, teacher training, and policy formulation. By bridging classical Islamic intellectual traditions with contemporary challenges, this study offers a contextually relevant and theoretically grounded model addressing the ethical and spiritual deficits of modern education, promoting learners who are ethically responsible, spiritually aware, and intellectually prepared for today’s complex society.